Perancangan Resort dengan Pendekatan Arsitektur Berkelanjutan di Kabupaten Serdang Bedagai - Sinta Marito Br. Panjaitan; Melly Andriana; Cut Nuraini (Pusat riset dan Inovasi Nasional, 2026)
The principle of sustainability is the main foundation in the development of a coastal resort in Mangrove Beach, Serdang Bedagai, which has high tourism potential but lacks environmentally friendly facilities. This study uses a sustainable architectural design method based on Biophilic design, which emphasizes human connection with nature through adaptive design and harmony with the environment. The implementation of this concept is realized through the use of locally sourced low- carbon materials, cross-ventilation, and natural lighting for energy efficiency, integration of vegetation as both aesthetic and ecological elements, environmentally friendly rainwater and waste management, and site planning that respects the coastal ecosystem. The design outcome is a resort with an organic form inspired by shells and ocean waves, creating an architectural identity that harmonizes with the area's character, providing a comfortable tourist experience for visitors, and contributing to local economic growth and environmental conservation, thereby serving as a concrete example of sustainable coastal tourism development in North Sumatra.